Antibiotic Prescribing Practices for Upper Respiratory Tract Infection Among Clinical Officers at Kiambu County - Kevin, Murigi; Joseph, Thigiti; Muiruri, King’ang’a (Journal of Family Medicine, 2024)
Background Antibiotics are the most prescribed medications worldwide. Global consumption rose by 65% in 76 low and middle-income countries between the years 2000 and 2015. According to the World Health Organization, improper administration of antibiotics occurs in over 60% of people with upper respiratory tract infections. Inadvertent antibiotic use has been identified as a contributor to antimicrobial resistance. Outpatient antibiotic use accounts for around 80-90% of all antibiotic use in patients. Clinical officers are non-physician healthcare workers who have received less training, have a more restricted scope of practice than physicians. Clinical officers are key service providers in this country especially at the primary healthcare level. Objective The study assessed the factors that influence antibiotic prescribing for upper respiratory tract infections by clinical officers. Method A prospective study was carried out at 20 public hospitals in Kiambu County, on 36 clinical officers and 600 patient prescriptions. The parameters measured were patient factors, prescriber factors, institutional factors and how they affected the antibiotic prescribing practices by either being rational or irrational. Rational prescribing was identified as prescribing the right drug, at the right frequency, in the right duration, right dose for the right indication. Prescriptions were considered irrational if they did not satisfy any of the rational indices. Data was collected via a questionnaire from the clinical officers while WHO prescription checklist was used to collect data from patient encounters. Data was analyzed using Statistical Package for Social Sciences version 22.0 (SPSS v22.0) with P-value, Confidence Interval and Odds Ratio. Results A total of 600 patient encounters were recorded and 79.8% of the 479 encounters had an antibiotic prescription for URTI, 91% of the antibiotics prescribed were the right dose, 98% had the right frequency, 75% had the right duration, and only 23% had the right indication. Patients above 65 years were more likely to receive an antibiotic prescription OR 3.98 CI 0.91,17.41 P=0.17 compared to children under 12 years old. Males were more likely to receive an antibiotic, but this was not significant OR 1.06 CI 0.70, 1.59 P=0.79. A total of 28 (4.6%) patients had fever, and all received antibiotics. A total of 36 clinical officers were sampled and only 5 (13.8%) were found to have rational prescriptions (P=0.63), prescriber age (P=0.92), prescriber level of education (P=0.99) and prescriber work experience (P=0.22) were not associated with antibiotic prescription. As per institutional factors, availability of antibiotics (P=0.026) and availability of prescription guidelines (P=0.012) were associated with rational prescription of antibiotics. Conclusion The study indicated that there was a high antibiotic prescription rate deviating from the WHO standard. It demonstrated that most antibiotic prescriptions were irrational.
Keywords: Antibiotics; clinical officers; upper respiratory tract infections